Study of the structure of the apical construction in different conditions of the canal-root system - T. N. Manak; K. G. Kliuyko (Эндодонтия Today)
Despite the achievements of modern dentistry, the question of choosing the apical termination point of root canals for endodontic treatment remains opened. It is known, that the inflammatory processes of the tooth pulp do not make a destructive effect on the apical constriction, when this inflammation is limited to the root canal. At the same time, the safety of the apical constriction in the tooth’s root canal with chronic apical periodontitis remains questionable because of the possibility of spreading destructive processes from the periapical tissues to the inner and outer surface of the tooth root. The article presents the results of studying the variability of apical constriction in healthy teeth, and also in teeth with apical periodontitis. A demonstration of an apical constriction on the "transparent tooth" model was made.